2000
DOI: 10.4049/jimmunol.165.10.5703
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies Directed Against the MHC-I Molecule H-2Dd Complexed with an Antigenic Peptide: Similarities to a T Cell Receptor with the Same Specificity

Abstract: αβ TCRs, which use an Ab-like structure to form a combining site, recognize molecular complexes consisting of peptides bound to MHC class I (MHC-I) or class II (MHC-II) molecules. To explore the similarities and differences between Ab and T cell recognition of similar structures, we have isolated two mAbs, KP14 and KP15, that specifically bind H-2Dd complexed with an HIV envelope gp160-derived peptide, P18-I10. These Abs are MHC and peptide specific. Fine specificity of mAb binding was analyzed using a panel o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 76 publications
0
42
0
Order By: Relevance
“…Endogenous Antigen-Monoclonal antibodies have been used previously to examine the presentation of specific pMHC (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Generation of such reagents is laborious and involves extensive screening of monoclonal antibodies, although some recent technical advances may facilitate this process (34,35).…”
Section: Tcr Multimers Can Sense Quantitative Modifications Of Antigementioning
confidence: 99%
“…Endogenous Antigen-Monoclonal antibodies have been used previously to examine the presentation of specific pMHC (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Generation of such reagents is laborious and involves extensive screening of monoclonal antibodies, although some recent technical advances may facilitate this process (34,35).…”
Section: Tcr Multimers Can Sense Quantitative Modifications Of Antigementioning
confidence: 99%
“…Two potent classes of reagents have been developed to bind to such complexes. Specific TCR, engineered from cloned T cells of known pMHC specificity, have been used to visualize cell surface pMHC complexes (4,5), and MHC-restricted, peptide-specific mAb, identified by various immunization and screening schemes, have been isolated and used similarly (5)(6)(7)(8)(9)(10)(11)(12). However, it has recently been suggested that in vitro selection of phage libraries displaying Ab fragments could be one of the most efficient ways to select specific pMHC binders (3).…”
mentioning
confidence: 99%
“…P18-I10 complexes on the surface of infected cells were analyzed with the KP15 mAb, which specifically recognizes the H-2D d -P18-I10 peptide complex (Polakova et al, 2000), using a three-step amplification method with biotinylated secondary antibody (BD Pharmingen, San Jose, CA) and PE-labeled Streptavidin (BD Pharmingen, San Jose, CA) as previously described (Dzutsev et al, 2007).…”
Section: Antibodies Tetramer Assays and Flow Cytometrymentioning
confidence: 99%
“…The H-2D d -restricted P18-I10 epitope is expressed by the gp160-containing recombinant vaccinia virus vPE16 and can be detected (Dzutsev et al, 2007) using the KP15 antibody, which recognizes the P18-I10/H-2D d complex (Polakova et al, 2000). In the culture of P815 cells 24h post infection with vPE16 all KP15 positive cells were also gp120 positive (Fig.2b); whereas VSC8-infected cells were negative by both KP15 and anti-gp120 staining (Fig.2a).…”
Section: Estimation Of the Frequency Of Vaccinia Virus-infected P815 mentioning
confidence: 99%
See 1 more Smart Citation